Preserving flexibility in IIAs : the use of reservations (UN New YorkUS, 2006)
Assesses the various means that IIA contracting parties have at their disposal when attempting to preserve flexibility and regulatory autonomy. Explores the revealed preferences for flexibility emerging from the reservation lists of eight IIAs employing a negative list approach to scheduling non-conforming measures.
Keywords: INVESTMENT